2013
DOI: 10.3390/rs5083826
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Assessment of Soil Erosion Risk Using Landsat TM and HJ Satellite Data in Danjiangkou Reservoir Area, China

Abstract: Danjiangkou reservoir area is the main water source and the submerged area of the Middle Route South-to-North Water Transfer Project of China. Soil erosion is a factor that significantly influences the quality and transfer of water from the Danjiangkou reservoir. The objective of this study is to assess the water erosion (rill and sheet erosion) risk and dynamic change trend of spatial distribution in erosion status and intensity between 2004 and 2010 in the Danjiangkou reservoir area using a multicriteria eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 52 publications
0
39
0
4
Order By: Relevance
“…These findings agree with those of the recent study by Uddin et al [90] who reported that the state of soil erosion risk in the Koshi Basin has been worsening following increase in the proportion of the eroded areas over 9.0% of the total basin area between 1990 and 2010. On the contrary, Wang et al [92] found improvement in the state of erosion risk in the Danjiangkou reservoir area, China, where the eroded areas have declined from 32.1% in 2004 to 25.43% in the 2010 study period. Moreover, Jiang et al [16] reported that the eroded area has Therefore, since there is geospatial variation in soil erosion risk distribution across the watershed area, identification of priority area is the key factor for planning and implementing appropriate SWC [10][11][12][13][14][15][16][17][18][19]51,90,142].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings agree with those of the recent study by Uddin et al [90] who reported that the state of soil erosion risk in the Koshi Basin has been worsening following increase in the proportion of the eroded areas over 9.0% of the total basin area between 1990 and 2010. On the contrary, Wang et al [92] found improvement in the state of erosion risk in the Danjiangkou reservoir area, China, where the eroded areas have declined from 32.1% in 2004 to 25.43% in the 2010 study period. Moreover, Jiang et al [16] reported that the eroded area has Therefore, since there is geospatial variation in soil erosion risk distribution across the watershed area, identification of priority area is the key factor for planning and implementing appropriate SWC [10][11][12][13][14][15][16][17][18][19]51,90,142].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, conservation priority levels were obtained to support the spatial planning and implementation of SWC measures in the study area. Prioritization was based on soil loss assessment results and change in erosion risk classes between 2000 and 2016 with the help of MCDR method [90][91][92]. We set the highest value for areas with a high and increasing risk of soil erosion.…”
Section: Development Of the Rusle Model Factorsmentioning
confidence: 99%
“…Soil erosion decreases exponentially with increase in vegetation cover (Jiang et al 2015;Shit et al 2013). Plant cover reduces soil erosion by intercepting raindrops, enhancing infiltration, slowing down the movement of runoff (Gyssels et al 2005;Wang et al 2013). The crop management factor (C) is the ratio of soil loss from an area with specified cover and management to soil loss from an identical area in tilled continuous fallow.…”
Section: Crop Management Factor (C)mentioning
confidence: 99%
“…As áreas frágeis distribuem-se em áreas com ausência de cobertura vegetal ou com baixa densidade de biomassa (solo exposto e campo limpo). Estas constatações corroboram com outros estudos que associam também a alta fragilidade à baixa biomassa e a declives mais acentuados (MORGAN, 1986 TRABUCCHI et al, 2012;WANG et al, 2013;XU et al, 2012.…”
Section: Resultsunclassified
“…A análise da distribuição espacial do risco à erosão do solo deve ser considerada como procedimento fundamental para o controle da erosão e proteção do ambiente ecológico (WANG et al, 2013). Neste sentido, diversos autores buscaram desenvolver modelos e métodos para mapear e identificar áreas suscetíveis a esta forma de degradação da paisagem.…”
Section: Introductionunclassified